The Role of Insight in Moderating the Association Between Depressive Symptoms in People With Schizophrenia and Stigma Among Their Nearest Relatives: A Pilot Study - Krupchanka, Dzmitry; Katliar, Mikhail (Schizophrenia bulletin, 2016)
BACKGROUND: There is evidence of a positive association between insight and depression among patients with schizophrenia. Self-stigma was shown to play a mediating role in this association. We attempted to broaden this concept by investigating insight as a potential moderator of the association between depressive symptoms amongst people with schizophrenia and stigmatizing views towards people with mental disorders in their close social environment. METHOD: In the initial sample of 120 pairs, data were gathered from 96 patients with a diagnosis of "paranoid schizophrenia" and 96 of their nearest relatives (80% response rate). In this cross-sectional study data were collected by clinical interview using the following questionnaires: "The Scale to Assess Unawareness of Mental Disorder," "Calgary Depression Scale for Schizophrenia," and "Brief Psychiatric Rating Scale." The stigmatizing views of patients' nearest relatives towards people with mental disorders were assessed with the "Mental Health in Public Conscience" scale. RESULTS: Among patients with schizophrenia depressive symptom severity was positively associated with the intensity of nearest relatives' stigmatizing beliefs ("Nonbiological vision of mental illness," τ = 0.24; P < .001). The association was moderated by the level of patients' awareness of presence of mental disorder while controlling for age, sex, duration of illness and psychopathological symptoms. CONCLUSIONS: The results support the hypothesis that the positive association between patients' depression and their nearest relatives' stigmatizing views is moderated by patients' insight. Directions for further research and practical implications are discussed.
Keywords: dospělí; Female; Social Stigma; rodina; awareness of illness; Adult; ženské pohlaví; stigma; průřezové studie; Schizophrenic Psychology; paranoidní schizofrenie; lidé; Pilot Projects; uvědomování si; pilotní projekty; společenské stigma; depression; Humans; Cross-Sectional Studies; Male; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; Family; insight; lidé středního věku; deprese; mužské pohlaví; Depression; Schizophrenia, Paranoid; schizofrenie (psychologie); Middle Aged; schizophrenia; Awareness